Risedronate and Follow-up Quantitative Ultrasound Reduces Refracture in Osteoporosis - Parry, Nicola (MD Conference Express, 2014)
This article presents results from a randomized trial demonstrating a reduction in subsequent fractures in patients with intertrochanteric fractures who were treated with risedronate and received follow-up care with quantitative ultrasound to monitor the existing fracture and bone status.